The Effect of Company Size, Company Age and Profitability on Earnings Management - Ni Made, Sri Ayuni; Novita Sari, Ni Luh Seni; Novi Budiasni, Ni Wayan (Moneter: Jurnal Keuangan dan Perbankan, 2024)
To find out the effect of company size, company age and profitability on earnings management is the target through this research at PT Edie Arta Motor Indonesia Branch Bungkulan. By using anuaall reports for fifth years consisting of 2018 to 2022. The analysis technique tested through several analyses, namely multiple linear regression, classical assumptions and hypotheses, model feasibility test.The results showed that company size had a negative and significant effect on earnings management at PT Edie Arta Motor Indonesia Branch Bungkulan, the size of a company can greatly influence the occurrence of earnings management practices, which can be seen from the overall assets owned by the company, it is very possible for earnings management practices to occur in the company. There is a positive effect of company age on earnings management PT Edie Arta Motor Indonesia Branch Bungkulan with the age owned by a company in running its business as seen from how much income or income the company earns every day, with this the company will be able to continue to grow along with the addition of assets or facilities (equipment) owned by the company. Profitability have a negative impact or influence on its profit management PT Edie Arta Motor Indonesia Branch Bungkulan with the profitability of the company being able to help the company continue to grow every month, the profitability of the company really helps company owners in knowing how far their company can compete with others.